Dynamis : Acta Híspanica ad Medícínae Scientiarumque Hístoriam lllustrandam (Departamento de Historia de la Medicina, Universidad de Granada, 1981)
Collectio operum quae in culturam et statum socialem professionis medicae in Europa XIX saeculo intendunt. Destinatus ad professionem publicam. A collection of works that focus on the culture and social status of the medical profession in 19th century Europe. Intended for the professional public.
Keywords: zaměstnání; lékařství; Social Values; profesionalita; History, 19th Century; Europe; sociální hodnoty; dějiny 19. století; sociální status; kultura; Medicine; Evropa; Culture; Occupations; Physicians; sociologie; lékaři; Professionalism; dějiny lékařství; Social Status